2023
DOI: 10.1111/bjet.13314
|View full text |Cite
|
Sign up to set email alerts
|

Fostering children's acceptance of educational apps: The importance of designing enjoyable learning activities

Abstract: Educational applications (apps) offer opportunities for designing learning activities children enjoy and benefit from. We redesigned a typical mobile learning activity to make it more enjoyable and useful for children. Relying on the technology acceptance model, we investigated whether and how implementing this activity in an app can increase children's intention to use. During the 27‐day study, children (N = 103, 9–14 years) used the app to memorize one‐sentence learning plans each day. Children used three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 83 publications
(135 reference statements)
0
0
0
Order By: Relevance
“…It is important to note that differences in needs might not only result from differing cognitive and metacognitive abilities, but also the context in which learning takes place, academic motivation, and emotions 50 . For children, perceived enjoyment of mobile interventions should also be ensured as it can predict their intention to actually engage with a given intervention 52 . Ideally, these and their dynamic changes should therefore also be taken into account 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that differences in needs might not only result from differing cognitive and metacognitive abilities, but also the context in which learning takes place, academic motivation, and emotions 50 . For children, perceived enjoyment of mobile interventions should also be ensured as it can predict their intention to actually engage with a given intervention 52 . Ideally, these and their dynamic changes should therefore also be taken into account 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The emoji-activity that we designed specifically for the app was perceived as more enjoyable to use and it was the activity that the participants would prefer to use more in the future. Further analysis of the dataset has also shown that this increased enjoyment results in an increased intention to use of the app (Amaefule et al, 2023). The limitation to the interpretation of the results from Paper 5 against the background of the digital distractions discussed here is that it was not explicitly about media use habits.…”
Section: The Challenges Of App-based Habit Buildingmentioning
confidence: 82%
“…Considering that motivation to use an app indicates a future intention to use it more (Amaefule et al, 2023), our PROMPT app is also an example of how to make an activity more enjoyable. The findings suggest that a child-appropriate planning app works but needs to be personalized and tailored to children's learning prerequisites in order to be effective.…”
Section: Resultsmentioning
confidence: 99%